2020
DOI: 10.24246/j.js.2020.v10.i3.p198-206
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Game-Based Learning Terhadap Motivasi dan Prestasi Belajar

Abstract: The curriculum requirement requires the lecturer to be creative in developing the learning style. However, in interpersonal skill subject, the lecturer only provides things that available on the textbook conventionally and focusing on the material accomplishment of the curriculum without considering the learning expected output. To resolve that problem, the lecturer needs to modify the learning style by providing a learning innovation. One of the alternatives is implementing game-based learning model by playin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 11 publications
4
12
0
12
Order By: Relevance
“…If the students have finished a game, they can proceed to the following games so that the mastery learning concept is also implemented in the multimedia developed. The results showed that game education was able to increase understanding, motivation and learning achievement [14], [15].…”
Section: Discussionmentioning
confidence: 99%
“…If the students have finished a game, they can proceed to the following games so that the mastery learning concept is also implemented in the multimedia developed. The results showed that game education was able to increase understanding, motivation and learning achievement [14], [15].…”
Section: Discussionmentioning
confidence: 99%
“…[3] Menurut Torrente game based learning merupakan suatu pembelajaran yang menggunakan metode permainan yang bertujuan untuk pendidikan, sebagai instrumen untuk mendukung proses pembelajaran secara signifikan (Pratiwi & Musfiroh, 2014). [4] Permainan memiliki 4 karakteristik utama dalam perspektif pendidikan, yaitu: 1. Hasil yang telah didapatkan oleh peserta didik setelah aktivitasnya dalam game.…”
Section: Jurnal Pendidikan Dan Teknologi Indonesia (Jpti)unclassified
“…Berada di kelas peserta didik merasa senang dan bersemangat saat mengerjakan soal-soal yang terdapat dalam words scramble game ini karena, dengan adanya words scramble game peserta didik dapat belajar sembari bermain atau yang sering disebut dengan game based learning. [4] Menurut Torente, pembelajaran berbasis permainan ialah suatu permainan yang memiliki tujuan khusus (tujuan pendidikan), yang berfungsi untuk mendukung proses pembelajaran secara signifikan. (Pratiwi &Musfiroh, 2014).…”
Section: E Tahap Evaluasiunclassified
“…Learning can be said as a process of interaction between students and teachers, which is supported by the existence of learning elements such as, infrastructure, learning materials, teacher teaching methods, applied models, school environmental conditions, and evaluations given by teachers (Winatha & Setiawan, 2020). All of these elements are needed in supporting the learning process, especially in the use of media, models, and learning methods.…”
Section: Introductionmentioning
confidence: 99%